Factors associated with healthcare utilization and trajectories in retirement village residents. Issue 3 (15th December 2021) - Bloomfield, Katherine; Wu, Zhenqiang; Broad, Joanna B.; Tatton, Annie; Calvert, Cheryl; Hikaka, Joanna; Boyd, Michal; Peri, Kathy; Bramley, Dale; Higgins, Ann‐Marie; Connolly, Martin J.
Abstract: Background: To study healthcare utilization and trajectories, and associated factors, in older adults in retirement villages (RVs), also known as continuing care retirement communities. Methods: Prospective cohort study of 578 cognitively intact residents from 34 RVs in Auckland, New Zealand (NZ). Measurement: InterRAI‐Community Health Assessment (includes core items that may trigger functional supplement (FS) completion in those with higher needs, and generates clinical assessment protocols (CAPs) in those with potential unmet needs). Outcomes: time to acute hospitalization, long‐term care (LTC), and death during average 2.5 years follow‐up. Results: Three hundred seven (53%) residents had acute hospitalizations, 65 (11%) moved to LTC, and 51 (9%) died over a mean of 2.5 years. Factors associated with increased risk of acute hospitalization included CAP‐falls (high risk) triggered, number of comorbidities, not having left RV in 2 weeks prior, moderate/severe hearing impairment, CAP‐cardiorespiratory conditions triggered, acute hospitalization in year prior and age, with significant hazard ratios (HR) ranging between 1.03 and 2.90. Factors associated with reduced risk of hospitalization included other (non‐NZ) European ethnicity (HR 0.73, 95% CI 0.55–0.98, p  = 0.04), presence of on‐site clinic (HR 0.62, 95% CI 0.45–0.85, p  = 0.003), no influenza vaccination (HR 0.56, 95% CI 0.38–0.83, p  = 0.004). Factors associated with LTC transition included FS triggered (HR 3.84, 95% CI 1.92–7.66, p  < 0.001), CAP‐instrumental activities of daily living (IADL) (HR 2.62, 95% CI 1.22–5.62, p  = 0.01), CAP‐social relationship triggered (HR 2.00, 95% CI 1.13–3.55, p  = 0.02), and age (HR 1.13, 95% CI 1.07–1.18 p  < 0.001). Factors associated with mortality included number of comorbidities (HR 3.75, 95% CI 1.54–9.10, p  = 0.004 for 3–5 comorbidities), CAP‐IADL triggered (HR 3.05, 95% CI 1.30–7.16, p  = 0.01), and age (HR 1.11, 95% CI 1.05–1.18, p  < 0.001). Conclusion: A large proportion of cognitively intact RV residents are admitted to hospital in mean 2.5 years of follow‐up. Multiple factors were associated with acute hospitalization risk. On‐site clinics were associated with reduced risk and should be considered in RV development.